The Importance of Academic Writing Knowledge To Second- Year Students to Foster Them Achieve University Success - Mechitoua, Nassima (Journal of Human Sciences, 2016)
Writing the different academic papers such as essays and articles at the university requires from students to follow certain conventions proper to formal and cautious academic writing. This paper aims to explore second-year students’ perceptions and attitudes of academic writing and its prominent features at the Department of Letters and English Language at the University of Constantine1. The choice of second year students is because they have been exposed to certain skills of writing in their first year, as how to write the different types of sentences and short paragraphs. For gathering data, two questionnaires were administered to eight teachers of writing, and to a population of sixty second-year students. The analysis of the data confirmed that students lack knowledge of the features of academic writing.